The Potential Use of Humic Acids - Didiek Hadjar Goenadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 1999)
The potential use of humic acids has received a great deal of attention during the last decade. Many research workers have suggested the advantage one can expect in the application of humic acids to provide a better growth of plants. Although their characteristics are subjected to considerable variation according to the sources from which they were extracted, the common effect of their application shows very convincing phenomena. However, such information is stilt limited in Indonesia resulting in a somewhat ignorance among the scientists in the country about the remarkable potential of the humic acid application. The objective of this discussion is, therefore, to elaborate basic information regarding the extraction techniques, characteristics variation, potential use as organic-N sources in the form of amino acids for carrier component of microbial inoculants and tissue culture media of plants, ion uptake enhancer, promoter of proteins and nucleic acids synthesis, and enzyme activator.